PRODUKSI BIO DIESEL DARI MINYAK JARAK PAGAR MELALUI PROSES ENSIMATIS - Dini Cahyandari; Muhammad E ndy Y (JURNAL LITBANG PROVINSI JAWA TENGAH, 2007)
Biodiesel ( methyl ester or Ethyl Ester) is the solution to the expensiveof fuel. Biodisel is produced from vegetable oil that the cost can be presser to the rational price. There are some material that can produce biodisel, like coconut oil, sun flower seed oil, soys oil, Jatrophacurcas oil and so on. Researcherchoose Jatropha curcas oil as basic material ofbiodisel because Jatropha curcas oil that produce from Jatropha curcas seed can grow easily on Indonesialand. On the other hand Jatropha curcas oil cannot use as consume oil so there are much oil for fuel than consume oil. The other reason is Jatropha curcas seed has much oil than other seed with enzyme from papaya lateksand bekatul that easyto find and lower cost. Researchmethods are project pilot of enzymatic reactor, study of'biodiesel productivity and optimize the process parameter.The hypothesis is the productionofbiodisel with chemical process have some problems. There are energy consuming, transesterification that not perfectand the difficulty to take glycerol product. These problem can be solved by using enzimatis method. Some vegetableoil have been use as biodiesel include jatropa curcas oil. From other researchcan be conclude that dependent factor to produce biodieselwith enzimatis method are kind of enzyme, water,methanol/oil ratio and themperaturfor sort time reaction.